Two-fluid effects on resistive wall modes in plasmas with negative versus positive triangularity - Xu Yang; Yueqiang Liu; Li Li; Jiao Yuan; Xin He; Yuling He; Guoliang Xia; Guanqi Dong (Nuclear Fusion)
The MARS-F code (Liu et al 2000 Phys. Plasmas 7 3681), has been updated to include two-fluid (2F) effects for linear stability analysis of magneto-hydrodynamic modes. The updated code, referred to as MARS-2F, is then applied to study flow stabilization of the resistive wall mode (RWM) in a reactor-scale negative-triangularity (NT) plasma, with the results also compared to that obtained in a positive-triangularity counterpart. The RWM is computed to be stable in plasmas with slow or even vanishing toroidal fluid flow according to the 2F-model, with much wider stability window for the NT plasma. This stability regime is attributed to the E × B flow stabilization, which is finite even at vanishing (single) fluid flow since the diamagnetic flow remains finite. This finding provides an alternative interpretation of the RWM stability in the slow-flow regime in tokamak plasmas as observed in experiments. Varying the fluid flow shear and a parallel sound wave damping model confirms the robustness of the 2F-model in predicting the stable window for the RWM in the slow-fluid-flow regime.